The Correlation Analysis Between Subjective and Objective Indicators of Physical Development of Students of 5th and 9th Grades - Ihor Bakiko; Tatiana Krutsevich; Vadym Smoliuk; Andrii Shevchuk (OVS LLC, 2022)
The study purpose was to investigate the correlation between the objective results of measurements of somatometric and physiometric indicators of physical development and the subjective indicators of its self-description for students of 5th and 9th grades. Materials and methods. The study was conducted in Lutsk secondary school 17 involving 120 secondary school students (aged 10 and 15) as participants. Research methods: analysis of data of scientific and methodical literature, normative-legal documents, programs on physical culture, pedagogical testing of physical fitness, methods of mathematical statistics, E.V. Bochenkova test-questionnaire "Self-description of physical development". Results. The correlation analysis between the results in mobility tests for strength, endurance, coordination and flexibility and self-assessment of these indicators by students of 5th and 9th grades shows that they differ. The 9th graders evaluate their physical abilities more objectively. This is due to gaining practical experience in physical education classes. The inadequacy of self-assessment of physical abilities shows that insufficient attention is paid to substantiating the importance of pedagogical control of physical fitness of students during the physical education classes. Conclusions. The study demonstrates the inadequacy of self-assessment of physical fitness by students, which indicates the importance of theoretical presentation and practical implementation in physical education classes of pedagogical control and self-control of physical fitness, which should be an incentive for boys and girls' self-improvement in physical education.